2022
DOI: 10.1063/5.0076970
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 2D perovskite (PMA)2PbI4 crystal and Cu ion implantation improved x-ray detector

Abstract: Two-dimensional (2D) perovskites have been demonstrated great promise in x-ray detection application because of their stability, tunability, and the unique electronic properties. The centimeter-sized 2D perovskite (PMA)2PbI4 single crystal and the corresponding x-ray detector were fabricated. The Cu ion implanted device exhibits an excellent sensitivity of 283 μC Gyair−1 cm−2, the significantly enhanced mobility-lifetime (μτ) product of 8.05 × 10−3 cm2 V−1, and the lowest detectable dose rate of 2.13 μGyair s−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…Chemie Forschungsartikel and smooth crystal surface, which verifies the high crystalline quality of 1-S (Figure S9d). [18]…”
Section: Methodsmentioning
confidence: 99%
“…Chemie Forschungsartikel and smooth crystal surface, which verifies the high crystalline quality of 1-S (Figure S9d). [18]…”
Section: Methodsmentioning
confidence: 99%
“…For RP 2D PSC, Feng et al reported a coplanar X-ray detector made of (PMA) 2 PbI 4 (PMA = phenylmethylammonium) with a sensitivity of 150 µC Gy air −1 cm −2 at 10 V bias, which increased to 283 µC Gy air −1 cm −2 at a 50 V bias under a 40 keV p soft X-ray. [11] Zhang et al demonstrated that (o-F-PEA) 2 PbI 4 2D PSCs device exhibited an improved sensitivity of ≈600 µC Gy air −1 cm −2 (20 V) and in-plane carrier mobility of 6.35 cm 2 V −1 s −1 compared to (PEA) 2 PbI 4 (0.74 cm 2 V −1 s -1 ). [12] For DJ 2D PSC, Shen et al [13] reported a coplanar sensitive 2D monolayered (NH 3 C 4 H 8 NH 3 ) PbI 4 PSC detector, showing a 242 µC Gy air −1 cm −2 under the 10 V bias/40 keV p with in-plane carrier mobility (17 cm 2 V −1 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…reported a coplanar X‐ray detector made of (PMA) 2 PbI 4 (PMA = phenylmethylammonium) with a sensitivity of 150 µC Gy air −1 cm −2 at 10 V bias, which increased to 283 µC Gy air −1 cm −2 at a 50 V bias under a 40 keV p soft X‐ray. [ 11 ] Zhang et al. demonstrated that (o‐F‐PEA) 2 PbI 4 2D PSCs device exhibited an improved sensitivity of ≈600 µC Gy air −1 cm −2 (20 V) and in‐plane carrier mobility of 6.35 cm 2 V −1 s −1 compared to (PEA) 2 PbI 4 (0.74 cm 2 V −1 s –1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated that Sb 2+ -ion doping into (PEA) 4 NaInCl 8 and (PEA) 2 CsNaInCl 7 2D perovskites can introduce self-trapped excitons in the [SbCl 6 ] 3– octahedron, which is the main reason for bright broadband emissions . In our previous work, we adopted Cu, Ag, C, N, H, and He ions to modify the Sr 2 VON 3 2D perovskite and Ba 3 SbI 3 , showing that ion implantation can enhance the device performance by improving the light absorption properties of the perovskite. , Furthermore, the Cu-ion implantation can decrease the exciton binding energy and band gap of the PMA 2 PbI 4 single crystal, which was used to improve the PMA 2 PbI 4 single-crystal-based X-ray detector performance . Therefore, we expect that the ion implantation method can be applied to enhance the BDAPbI 4 -based photodetector performance.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Furthermore, the Cu-ion implantation can decrease the exciton binding energy and band gap of the PMA 2 PbI 4 single crystal, which was used to improve the PMA 2 PbI 4 single-crystal-based X-ray detector performance. 22 Therefore, we expect that the ion implantation method can be applied to enhance the BDAPbI 4 -based photodetector performance. Herein, we have grown centimeter-sized BDAPbI 4 single crystals by the low-temperature-gradient crystallization method.…”
Section: Introductionmentioning
confidence: 99%